Patchwork Innovation: A Study of Social Bricolage and Social Value Creation in Indonesia's Social Enterprises - Meiliana Jaunanda (Universitas Pelita Harapan, 2025)
The concept of social bricolage highlights creativity, flexibility, and boldness in utilizing available resources as the core of the social entrepreneurship process. In developing countries like Indonesia, publicly listed companies occupy a strategic position as social development actors through hybrid models that integrate profit-making with social impact. This article critically and reflectively analyzes the application of social bricolage theory (Di Domenico et al., 2010) in three Indonesian public companies—PT Telkom Indonesia, PT Pertamina (Persero), and PT Bank Rakyat Indonesia (Persero) Tbk—using a case-based reflective essay approach. Five key dimensions—making do, improvisation, refusal to be constrained, stakeholder participation, and persuasion—are explored within the dynamic tension between commercial interests and social missions, as well as institutional challenges that shape the practice of social value creation. The findings suggest that implementing social bricolage in large-scale corporations is not only feasible but also represents an adaptive strategy in navigating the social complexities and regulatory pressures typical of emerging markets like Indonesia.